2020
DOI: 10.1021/acs.chemmater.9b05366
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship between Effective Mass, Transient Photoconductivity, and Photocatalytic Activity of SrxPb1–xBiO2Cl (x = 0–1) Oxyhalides

Abstract: Owing to the rapid advancement in computer hardware and quantum chemical software, chemists can relatively easily calculate the electronic properties of semiconducting photocatalysts. However, these computed parameters do not always govern the overall photocatalytic activity of semiconductors because of the complexity of photochemical reactions and other undesired factors. Here, we explore the relationship between the effective mass of the charge carrier (m*) calculated by density functional theory (DFT), tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 48 publications
2
32
0
Order By: Relevance
“…Furthermore, the relationship among the calculated m*, experimental μ, and photocatalytic activity has remained elusive because of the abovementioned complexity of photocatalytic systems. However, this relationship was revealed in PbBiO 2 Cl and SrBiO 2 Cl photocatalysts, where the mixing of Sr and Pb formed a solid solution at arbitrary ratios [62]. Both m h * and m e * calculated by DFT increased with increasing Pb content, which corresponded to decreases in φΣμ max (the change in τ 1/2 is insignificant) and the oxygen evolution rate.…”
Section: C12-odmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, the relationship among the calculated m*, experimental μ, and photocatalytic activity has remained elusive because of the abovementioned complexity of photocatalytic systems. However, this relationship was revealed in PbBiO 2 Cl and SrBiO 2 Cl photocatalysts, where the mixing of Sr and Pb formed a solid solution at arbitrary ratios [62]. Both m h * and m e * calculated by DFT increased with increasing Pb content, which corresponded to decreases in φΣμ max (the change in τ 1/2 is insignificant) and the oxygen evolution rate.…”
Section: C12-odmentioning
confidence: 96%
“…In addition to an increased sensitivity of the resonant cavity, the direction of the electric field inside is fixed. Based on this property, anisotropic photoconductivity and mobility along various sample directions (parallel and perpendicular to a film and the xyz axes of a crystal) are easily evaluated with a high angular resolution [50][51][52][53][54][55][56][57][58][59][60][61][62].…”
Section: Design and Synthesis Device Fabricaɵonmentioning
confidence: 99%
“…3b, indicating an intense signal for the in-plane direction, with a maximum value of photoconductivity φ∑μ being 17 times higher. Provided that φ is constant (supported by the fact that the photoexcitation for carrier generation is fixed throughout the experiment), the S23) shows that both the CB and VB have greater dispersion along the in-plane directions (Г-X and Г-Y) than the out-of-plane direction (Г-Z), in common with layered materials (e.g., PbBiO 2 Cl 24 and Sr 2 TaO 3 N 40 ). However, a closer look reveals that the CB is more dispersive than the VB, and the effective mass of electrons (0.25 m 0 ) is smaller than that of holes (1.4 m 0 ).…”
Section: Site-selective Deposition Of Metal Cocatalystmentioning
confidence: 96%
“…Layered semiconductors such as UV-responsive K 4 Nb 6 O 17 have shown promise in photocatalysis 4,15,16 with a couple of advantages, including their controllability of the chemical composition through ion exchange [17][18][19] and large surface-tovolume ratios. 20 However, from the viewpoint of efficient charge separation inside the photocatalysts, two-dimensional crystal structures may be unfavorable because both photoexcited electrons and holes travel mainly along the inplane direction, as observed theoretically [21][22][23][24] and experimentally. [25][26][27] Such parallel carrier flows based on the crystal and band structure make it difficult to separate the oxidation and reduction reaction sites in the photocatalyst particles, often resulting in charge recombination.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of other structurally related layered oxyhalide systems suggested that the band structure can be controlled by changing the building layers and stacking sequence. [ 89–94 ] Recent developments in synthesis methods of these materials, including solid‐state reaction, polymerized complex method and flux methods, [ 95–98 ] and spectroscopic studies on the effect of structural differences on carrier dynamics [ 99,100 ] have allowed the development of stable Sillén–Aurivillius‐related photocatalysts with higher photocatalytic activity.…”
Section: Band‐engineered Sillén–aurivillius‐related Layered Oxyhalidesmentioning
confidence: 99%